Device characterization of cadmium telluride photovoltaics - Geisthardt, Russell M., author; Sites, James, advisor; Gelfand, Martin, committee member; Topič, Marko, committee member; Sampath, W. S., committee member (Colorado State University. Libraries, 2014)
Thin-film photovoltaics have the potential to make a large impact on the world energy supply. They can provide clean, affordable energy for the world. Understanding the device physics and behavior will enable increases in efficiency which will increase their impact. This work presents novel approaches for evaluating efficiency, as well as a set of tools for in-depth whole-cell and uniformity characterization. The understanding of efficiency losses is essential for reducing or eliminating the losses. The efficiency can be characterized by a breakdown into three categories: solar spectrum, optical, and electronic efficiency. For several record devices, there is little difference in the solar spectrum efficiency, modest difference in the optical efficiency, and large difference in the electronic efficiency. The losses within each category can also be further characterized. The losses due to the broad solar spectrum and finite temperature are well understood from a thermodynamic physics perspective. Optical losses can be fully characterized using quantum efficiency and optical measurements. Losses in fill factor can be quantified from series and shunt resistance, as well as the expected fill factor from the measured V oc and A. Open-circuit voltage losses are the most significant, but are also be the hardest to understand, as well as the most technology-dependent. Characterization of the whole cell helps to understand the behavior, performance, and properties of the cell. Several different tools can be used for whole-cell characterization, including current-voltage, quantum efficiency, and capacitance measurements. Each of these tools give specific information about the behavior of the cell. When combined, they can lead to a more complete understanding of the cell performance than when taken individually. These tools were applied to several specific CdTe experiments. They have helped to characterize the baseline performance of both the deposition tool and the measurement systems. Characterization of plasma-cleaned cells show an improvement in performance, even at thinner CdS layer thickness. Measurements of thinning CdTe samples reveal additional optical losses, likely caused by the increasing importance of the back diode. Characterization of Cd(S,O) devices show improved performance, both from improved optical properties and theorized improvement in band alignment properties. Uniformity can have an effect on whole-cell performance, but can also be an important parameter to characterize on its own. Light-beam-induced current is a powerful tool for characterizing uniformity. The LBIC tool was upgraded to improve its accuracy, functionality, and speed. The improved LBIC system aids in the collection of uniformity data. A number of parameters can be varied to provide in-depth uniformity information and help identify causes of nonuniformity. The wavelength can be varied to provide information on different layers. This can help identify variations in CdS thickness and local CdTe band gap. An applied voltage bias can be used to identify locations with weak diode properties. The resolution can also be varied to provide information on nonuniformities at different scales, from variations across the whole cell to variations on the size of several grains. LBIC can also be paired with electroluminescence to create a powerful nonuniformity characterization suite. The two can be paired with EL used as a screening tool to identify cells or areas which need further characterization from LBIC.
Keywords: cadmium telluride; solar cells; photovoltiacs; device physics